2015
DOI: 10.2174/138920021610151210164501
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metabolic Enzymes P450 (CYP) on Activating Procarcinogen and their Polymorphisms on the Risk of Cancers

Abstract: Cytochrome P450 (CYP450) enzymes are the most important metabolizing enzyme family exists among all organs. Apart from their role in the deactivation of most endogenous compounds and xenobiotics, they also mediate most procarcinogens oxidation to ultimate carcinogens. There are several modes of CYP450s activation of procarcinogens. 1) Formation of epoxide and diol-epoxides intermediates, such as CYP1A1 and CYP1B1 mediates PAHs oxidation to epoxide intermediates; 2) Formation of diazonium ions, such as CYP2A6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 148 publications
(219 reference statements)
1
43
0
Order By: Relevance
“…Because the main role of this enzyme is to metabolize environmental carcinogens, such as PAHs, heterocyclic amines, aflatoxin B1 and estrogen [37], variations within CYP1A1 gene may induce the occurrence of CRC. Currently, a widely accepted paradigm for CYP1A1 enzyme mediated carcinogens activation is that CYP1A1 metabolizes polycyclic aromatic hydrocarbons to reactive epoxide intermediates, which could covalently bind to DNA and then induce tumors [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Because the main role of this enzyme is to metabolize environmental carcinogens, such as PAHs, heterocyclic amines, aflatoxin B1 and estrogen [37], variations within CYP1A1 gene may induce the occurrence of CRC. Currently, a widely accepted paradigm for CYP1A1 enzyme mediated carcinogens activation is that CYP1A1 metabolizes polycyclic aromatic hydrocarbons to reactive epoxide intermediates, which could covalently bind to DNA and then induce tumors [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Rat serum ALT and AST levels significantly increased in the group with the administration of PMR and CYP1A2 or CYP2E1 inhibitor compared with all control groups at 1 d, 3 d, 5 d, 7 d, and 22 d, but no greater than twofold, which suggested that PMR related hepatotoxicity that happened in clinic might be due to some people with lower activities of CYP1A2 or CYP2E1 from genetic polymorphism [22, 23]. Actually, there was a clinical report which suggested that PMR induced hepatotoxicity may relate to low activity of CYP1A2 [28].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A2 and CYP2E1 mainly exist in the liver, accounting for 13% and 7% of total CYP450 enzymes, respectively [21]. In addition, CYP1A2 and CYP2E1 exhibit genetic polymorphism in the population [22, 23]. At least 23 allele genes of CYP1A2 have been found so far, and the major mutants are CYP1A2 ∗ 1C, CYP1A2 ∗ 1D, CYP1A2 ∗ 1F, CYP1A2 ∗ 1K, CYP1A2 ∗ 7, and CYP1A2 ∗ 11.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ishikawa and colleagues [51] showed that subjects carrying the ALDH2*2 allele who consumed ethanol more than three times per week had greater DNA damage, as reflected by an increased micronuclei frequency. Furthermore, cytochrome P450 (CYP2E1), which is known to form reactive oxygen species [52] and enhance pro-carcinogen activation [53], is upregulated in Aldh2 knockout mice, and is further induced by ethanol administration [54]. As such, ALDH2*2 has the potential to promote the risk of cancers induced by alcohol consumption (Fig.…”
Section: Effect Of Aldh2*2 On Cancerous Diseasesmentioning
confidence: 99%